2022
DOI: 10.1186/s12957-022-02585-3
|View full text |Cite
|
Sign up to set email alerts
|

KIF14 affects cell cycle arrest and cell viability in cervical cancer by regulating the p27Kip1 pathway

Abstract: Background Cervical cancer is a kind of malignant gynecological tumor. The first choice for treating cervical cancer is still a combination of surgery and chemoradiotherapy, but the 5-year survival rate remains poor. Therefore, researchers are trying to find new ways to diagnose and treat cervical cancer early. Methods The expression level of KIF14 in cells and tissues was determined via qRT–PCR. The ability of the cells to proliferate, migrate, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Knockdown experiments have shown that KIF14 suppression inhibits cell proliferation and induces apoptosis through inactivation of AKT signaling [ 24 ]. KIF14 has been associated with cervical cancer, and a knockdown model of KIF14 impacted the cell cycle by affecting cell viability, proliferation, and migration, thus placing it as a potential therapeutic target [ 70 ]. KIF14 has not yet been associated with SARS-CoV-2 infection, but it does interact with nsp9 and nsp4 ( Figure 3 B).…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown experiments have shown that KIF14 suppression inhibits cell proliferation and induces apoptosis through inactivation of AKT signaling [ 24 ]. KIF14 has been associated with cervical cancer, and a knockdown model of KIF14 impacted the cell cycle by affecting cell viability, proliferation, and migration, thus placing it as a potential therapeutic target [ 70 ]. KIF14 has not yet been associated with SARS-CoV-2 infection, but it does interact with nsp9 and nsp4 ( Figure 3 B).…”
Section: Discussionmentioning
confidence: 99%
“…KIF14 can act as a chromokinesin via binding to microtubules and chromatin during the bipolar spindle formation. Many studies have reported that KIF14 could promote tumorigenesis and progression by acting on many signaling pathways ( Yang et al, 2019 ; Zhang J. et al, 2022 ). Zhang J. et al (2022) found that KIF14 is an oncogene in cervical cancer, and knocking down KIF14 causes cell cycle arrest by inhibiting p27 degradation, thus affecting cell viability, proliferation, and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that KIF14 could promote tumorigenesis and progression by acting on many signaling pathways ( Yang et al, 2019 ; Zhang J. et al, 2022 ). Zhang J. et al (2022) found that KIF14 is an oncogene in cervical cancer, and knocking down KIF14 causes cell cycle arrest by inhibiting p27 degradation, thus affecting cell viability, proliferation, and migration. Similarly, silencing of KIF14 repressed tumor cell growth by interfering with cytokinesis and the p27Kip1 ubiquitination pathway in hepatocellular carcinoma ( Xu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Belonging to the kinesin-3 family, the functions of kinesin family member 14 (KIF14) are also dependent on microtubules. Notably, KIF14 has been proposed as a tumor promoter in multiple human malignancies, including cervical cancer ( 18 ), gastric cancer ( 19 ) and retinoblastoma ( 20 ). Notably, Wang et al has suggested that KIF14, targeted by microRNA (miR)-200c, activates Akt to elicit pro-proliferation activities in CRC ( 21 ).…”
Section: Introductionmentioning
confidence: 99%